2009
DOI: 10.1111/j.1365-277x.2008.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring issues influencing the use of the Malnutrition Universal Screening Tool by nurses in two Australian hospitals

Abstract: Background:  Nutrition screening using evidence‐based clinical practice is important for identifying patients whose nutritional status may be compromised, so that they receive appropriate treatment. Introduction of the Malnutrition Universal Screening Tool (`MUST') in two wards in two Melbourne hospitals resulted in low screening completion rates by nursing staff. Nurses’ screening practices were explored to understand personal and workplace barriers to compliance. Methods:  Surveys of patients’ medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 31 publications
2
89
0
6
Order By: Relevance
“…One action to overcome barriers with nutritional screening would be to program the calculation of BMI, percent weight loss and nutritional risk score into IT systems or allowing patients to input this data remotely supporting self-management; thereby reducing the amount of time the process takes. Patients could be given the option to screen at home as an alternative to screening during clinical visits [8,24], which would serve not only to reduce the burden on healthcare staff but also empower patients to be more involved in their own care [25]. However such a process would require availability of dietetic resources to formally review high risk cases.…”
Section: Discussionmentioning
confidence: 99%
“…One action to overcome barriers with nutritional screening would be to program the calculation of BMI, percent weight loss and nutritional risk score into IT systems or allowing patients to input this data remotely supporting self-management; thereby reducing the amount of time the process takes. Patients could be given the option to screen at home as an alternative to screening during clinical visits [8,24], which would serve not only to reduce the burden on healthcare staff but also empower patients to be more involved in their own care [25]. However such a process would require availability of dietetic resources to formally review high risk cases.…”
Section: Discussionmentioning
confidence: 99%
“…Porter et al 65 also reported low rates of compliance in 2 hospital wards as 17% and 62% in a survey of 46 admitted patients in Australia. The low compliance rate in this study also suggests that implementation of a nutrition screening tool within patient admission procedures does not automatically translate into nursing practice.…”
Section: Discussionmentioning
confidence: 90%
“…Sağlık personelinin bu konuyla ilgili bilgi eksikliklerinin olduğu, rehberleri, protokolleri kullanmadıkları ve zamanlarının olmayışı da neden olarak gösterilmiş-tir. 28,39,40 Bu bulgular çalışmamızla benzerlik göstermektedir. Bizim hastanemizde de konuyla ilgili rehberler ve yazılı protokollerin bulunmayışı, bilgi eksikliğinin nedeni olarak gösterilebilir.…”
Section: Tartişma Ve Sonuçunclassified
“…Zaman kısıtlılığı ve kaynağa nasıl ulaşılacağını bilememek bunlardan bazılarıdır. 28,40 Özellikle klinik uygulama rehberlerinin bakıma entegre edilmesi ile hasta bakımının kalitesinin artacağı ve bireyselleştirilmiş bakımın uygulanabileceği yapılan çalışmalarla gösterilmiş-tir. 42,43 Çalışmamızda son iki yılda bilimsel makale/kitap okuyanların bilgi puan ortalamaları yüksek olup, aradaki fark istatistiksel olarak anlamlı bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified